Status of Ulnar Nerve in Patients After Open Reduction Surgery Internal Fixation of Distal Humerus Fracture at Adam Malik Hospital Medan - Aga Shahri Putera Ketaren; Muhammad Hidayat Siregar; Rama Dhanianda Siregar (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Background: Distal humerus fractures are complex injuries that often require internal fixation open reduction surgery (ORIF). One of the complications that often accompanies is an ulnar nerve injury, which is reportedly related to the surgical approach technique. This study aims to analyze the relationship between the type of surgical approach and the incidence of post-ORIF ulnar nerve injury in distal humerus fractures. Methods: An analytical observational study with a cross-sectional design was conducted on 45 patients undergoing distal humerus fracture ORIF at Adam Malik Hospital Medan for the 2020-2024 period. Data were collected from medical records and postoperative neuroimaging results using McGowan's classification. The surgical approaches studied are: paratricipital, triceps splitting, Chevron osteotomy. Results: The mean age of patients was 42.02±12.46 years, with the majority being male (60%). The most frequent injury mechanism was falling (46.67%). The paratricipital approach is most commonly used (44.44%), followed by chevron osteotomy (35.56%) and triceps splitting (20%). Postoperative ulnar nerve injury was found in 3 patients (6.67%), with the highest proportionally incidence on the triceps splitting approach (11.1%). Analysis with Kolmogorov-Smirnov showed an insignificant association between surgical approach and ulnar nerve injury (p = 0.786). Conclusions: No significant association was found between the surgical approach of ORIF and the incidence of ulnar nerve injury. These findings may be a consideration in the selection of a safe surgical approach to the ulnar nerve in distal humerus fractures.